Hot-rolled steel plate
Patent Information
- Application Number
- KR1020247019285
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-12-15
- Filing Date
- 2022-12-06
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2042-12-06
Smart Images

Figure 112024062141846-PCT00001 
Figure 112024062141846-PCT00002 
Figure 112024062141846-PCT00003
Abstract
Description
Technology Field
[0001] The present invention relates to hot-rolled steel sheets.
[0002] The present application claims priority based on Japanese Patent Application No. 2021-203094 filed in Japan on December 15, 2021, and incorporates the contents thereof herein by reference. Background Technology
[0003] From the perspective of protecting the global environment, vehicle bodies are being lightweighted to improve fuel efficiency. To further lighten vehicle bodies, it is necessary to increase the strength of the steel sheets used in the bodies. However, generally, increasing the strength of steel sheets reduces formability.
[0004] One method to improve the formability of steel sheets is to incorporate residual austenite into the metal structure. However, while incorporating residual austenite into the metal structure improves ductility, it may lead to a deterioration in bendability. When performing bending forming, excellent bendability is required in addition to excellent ductility.
[0005] Patent Document 1 discloses a hot-rolled steel sheet with excellent local deformation ability and excellent ductility with low orientation dependency of formability, and a method for manufacturing the same. Prior art literature
[0006] Japanese Patent Publication No. 5533729 The problem to be solved
[0007] The inventors have found that there is a need to further increase the ductility and bendability of the hot-rolled steel sheet described in Patent Document 1.
[0008] The present invention has been made in consideration of the above circumstances and aims to provide a hot-rolled steel sheet having high strength and excellent ductility and bendability. means of solving the problem
[0009] With the above-mentioned problem in mind, the inventors have conducted extensive research on the relationship between the chemical composition, metal structure, and mechanical properties of hot-rolled steel sheets. As a result, they obtained the following findings and completed the present invention.
[0010] In order to incorporate residual austenite into the metal structure of a steel sheet, it is effective to increase the Si content. However, if the Si content is increased, scale may remain after descaling during hot rolling, which causes the bendability of the hot-rolled steel sheet to deteriorate. The inventors have discovered that the deterioration of bendability caused by residual scale can be suppressed by controlling the texture and surface characteristics of the hot-rolled steel sheet.
[0011] The gist of the present invention, based on the above findings, is as follows.
[0012] (1) A hot-rolled steel sheet according to one embodiment of the present invention has a chemical composition in mass%,
[0013] C: 0.100 to 0.350%,
[0014] Si: 0.30 to 3.00%,
[0015] Mn: 1.00 to 4.00%,
[0016] sol.Al: 0.001 to 2.000%,
[0017] Si+sol.Al: 1.00 to 5.00%,
[0018] P: 0.100% or less,
[0019] S: 0.0300% or less,
[0020] N: 0.1000% or less,
[0021] O: 0.0100% or less,
[0022] Ti: 0 to 0.380%,
[0023] Nb: 0 to 0.100%,
[0024] V: 0 to 0.500%,
[0025] Cu: 0 to 2.00%,
[0026] Cr: 0 to 2.00%,
[0027] Mo: 0 to 1.00%,
[0028] Ni: 0 to 2.00%,
[0029] B: 0 to 0.0100%,
[0030] Ca: 0 to 0.0200%,
[0031] Mg: 0 to 0.0200%,
[0032] REM: 0 to 0.1000%,
[0033] Bi: 0 to 0.020%,
[0034] One or more of Zr, Co, Zn, and W: 0 to 1.00% in total, and
[0035] Sn: Contains 0 to 0.050%,
[0036] The remainder consists of Fe and impurities, and
[0037] Metal structure, in area %
[0038] Bainite: 55 to 95%,
[0039] Retained austenite: 5 to 30%,
[0040] Fresh martensite: 5% or less,
[0041] Ferrite: 5% or less, and
[0042] Perlite: Consists of 5% or less, and
[0043] In the texture of the surface to the region at a depth of 1 / 8 of the plate thickness from the surface, the extreme density of {110}<111> orientation is 3.0 or less, and
[0044] The arithmetic mean roughness Ra of the above surface after pickling is less than 1.2㎛.
[0045] (2) The hot-rolled steel sheet described in (1) above has the chemical composition in mass%,
[0046] Ti: 0.005 to 0.380%,
[0047] Nb: 0.005 to 0.100%,
[0048] V: 0.005 to 0.500%,
[0049] Cu: 0.01 to 2.00%,
[0050] Cr: 0.01 to 2.00%,
[0051] Mo: 0.01 to 1.00%,
[0052] Ni: 0.02 to 2.00%,
[0053] B: 0.0001 to 0.0100%,
[0054] Ca: 0.0005 to 0.0200%,
[0055] Mg: 0.0005 to 0.0200%,
[0056] REM: 0.0005 to 0.1000%, and
[0057] Bi: 0.0005 to 0.020%
[0058] It may contain one or more types selected from the group consisting of Effects of the invention
[0059] According to the above embodiment of the present invention, a hot-rolled steel sheet having high strength and excellent ductility and bendability can be provided. Specific details for implementing the invention
[0060] The chemical composition and metal structure of the hot-rolled steel sheet according to the present embodiment are described in more detail below. However, the present invention is not limited to the configuration disclosed in the present embodiment, and various modifications are possible within the scope of the spirit of the present invention.
[0061] In the numerical limit ranges described below separated by "to," lower and upper limits are included. In numerical values indicated as "less than" or "greater than," those values are not included in the numerical range. In the following description, % regarding the chemical composition of the steel sheet is mass % unless specifically designated otherwise.
[0062] Chemical composition
[0063] The chemical composition of the hot-rolled steel sheet according to the present embodiment comprises, in mass%, C: 0.100 to 0.350%, Si: 0.30 to 3.00%, Mn: 1.00 to 4.00%, sol.Al: 0.001 to 2.000%, Si+sol.Al: 1.00 to 5.00%, P: 0.100% or less, S: 0.0300% or less, N: 0.1000% or less, O: 0.0100% or less, and the remainder: Fe and impurities.
[0064] Below, each element is explained in detail.
[0065] C: 0.100 to 0.350%
[0066] C is an element necessary to obtain the desired strength. If the C content is less than 0.100%, it becomes difficult to obtain the desired strength. Therefore, the C content is set to 0.100% or more. The C content is preferably 0.120% or more or 0.150% or more.
[0067] On the other hand, if the C content exceeds 0.350%, the transformation rate slows down, making it easy for MA (a mixed phase of martensite and retained austenite) to form, which makes it difficult to obtain excellent ductility. Therefore, the C content is set to 0.350% or less. The C content is preferably 0.330% or less, 0.310% or less, 0.300% or less, or 0.280% or less.
[0068] Si: 0.30 to 3.00%
[0069] Si has the effect of delaying the precipitation of cementite. Due to this effect, the amount of austenite remaining in an untransformed state, that is, the area ratio of retained austenite, can be increased. Furthermore, by maintaining a high amount of dissolved carbon in the hard phase and preventing the coarsening of cementite, the strength of the hot-rolled steel sheet can be increased. In addition, Si itself has the effect of increasing the strength of the hot-rolled steel sheet through solid solution strengthening. Furthermore, Si has the effect of soundening the steel through deoxidation (suppressing the occurrence of defects such as blowholes in the steel). If the Si content is less than 0.30%, the effect due to the above action cannot be obtained. Therefore, the Si content is 0.30% or more. The Si content is preferably 0.50% or more, 1.00% or more, 1.20% or more, or 1.50% or more.
[0070] On the other hand, if the Si content exceeds 3.00%, it is undesirable because it significantly delays the precipitation of cementite, resulting in an excessive amount of retained austenite. Furthermore, the surface properties and chemical treatability of the hot-rolled steel sheet, as well as ductility and weldability, deteriorate significantly, and the A3 transformation point rises significantly. Consequently, it becomes difficult to perform hot rolling stably. Therefore, the Si content is set to 3.00% or less. The Si content is preferably 2.70% or less, or 2.50% or less.
[0071] Mn: 1.00 to 4.00%
[0072] Mn has the effect of suppressing ferrite transformation to increase the strength of hot-rolled steel sheets. If the Mn content is less than 1.00%, the desired strength cannot be obtained in the hot-rolled steel sheet. Therefore, the Mn content is 1.00% or more. The Mn content is preferably 1.30% or more, 1.50% or more, 1.80% or more, 2.00% or more, or 2.40% or more.
[0073] Meanwhile, if the Mn content exceeds 4.00%, the ductility of the hot-rolled steel sheet deteriorates. Therefore, the Mn content is set to 4.00% or less. The Mn content is preferably 3.70% or less, 3.50% or less, 3.30% or less, or 3.00% or less.
[0074] sol.Al: 0.001 to 2.000%
[0075] Sol.Al, like Si, has the effect of deoxidizing the steel to sounden the steel sheet and, at the same time, promoting the formation of residual austenite by suppressing the precipitation of cementite from austenite. If the sol.Al content is less than 0.001%, the effect of the above action cannot be obtained. Therefore, the sol.Al content is 0.001% or more. The sol.Al content is preferably 0.010% or more.
[0076] Meanwhile, if the sol.Al content exceeds 2.000%, the above effect becomes saturated and is not economically desirable. In addition, the A3 transformation point rises significantly, making it difficult to perform hot rolling stably. Therefore, the sol.Al content is kept at 2.000% or less. The sol.Al content is preferably 1.500% or less, or 1.300% or less.
[0077] In addition, in this embodiment, sol.Al means acid-soluble Al and represents solid solution Al existing in the steel in a solid solution state.
[0078] Si+sol.Al: 1.00 to 5.00%
[0079] Both Si and sol.Al have the effect of delaying the precipitation of cementite, and through this effect, the amount of austenite remaining in an untransformed state, that is, the area ratio of retained austenite, can be increased. If the total content of Si and sol.Al is less than 1.00%, the effect of the above action cannot be obtained. Therefore, the total content of Si and sol.Al is 1.00% or more. Preferably, it is 1.20% or more and 1.50% or more.
[0080] The total content of Si and sol.Al may be 5.00% or less, 3.00% or less, or 2.60% or less.
[0081] In addition, Si in “Si+sol.Al” represents the content of Si in mass%, and sol.Al represents the content of sol.Al in mass%.
[0082] P: 0.100% or less
[0083] P is an element generally contained in steel as an impurity, but it has the effect of increasing the strength of hot-rolled steel sheets through solid solution strengthening. Therefore, it is acceptable to actively include P. However, P is an element prone to segregation, and if the P content exceeds 0.100%, the decrease in ductility of the hot-rolled steel sheet caused by grain boundary segregation becomes significant. Therefore, the P content is kept at 0.100% or less. The P content is preferably 0.050% or less, or 0.030% or less.
[0084] There is no need to specifically specify a lower limit for the P content, but it may be 0%. From the perspective of refining costs, it is desirable to have a P content of 0.001% or more.
[0085] S: 0.0300% or less
[0086] S is an element generally contained in steel as an impurity, and it forms sulfide inclusions in the steel, thereby reducing the ductility of hot-rolled steel sheets. If the S content exceeds 0.0300%, the ductility of the hot-rolled steel sheet is significantly reduced. Therefore, the S content is kept at 0.0300% or less. The S content is preferably 0.0100% or less and 0.0050% or less.
[0087] There is no need to specifically specify a lower limit for the S content, but it may be 0%. From the perspective of refining costs, it is desirable to have an S content of 0.0001% or more.
[0088] N: 0.1000% or less
[0089] N is an element generally contained in steel as an impurity and has the effect of reducing the ductility of hot-rolled steel sheets. If the N content exceeds 0.1000%, the ductility of the hot-rolled steel sheet is significantly reduced. Therefore, the N content is set to 0.1000% or less. The N content is preferably 0.0800% or less, or 0.0700% or less. There is no need to specifically specify a lower limit for the N content, but it may be 0%. To promote the precipitation of carbonitrides, it is preferable to have an N content of 0.0010% or more, and more preferable to have an N content of 0.0020% or more.
[0090] O: 0.0100% or less
[0091] When O is contained in large quantities in steel, it forms coarse oxides that serve as fracture initiation points, causing brittle fracture or hydrogen-induced cracking. Therefore, the O content should be 0.0100% or less. It is preferable to keep the O content 0.0080% or less and 0.0050% or less.
[0092] In order to disperse a large amount of fine oxides during the deoxidation of molten steel, the O content may be 0.0005% or more, or 0.0010% or more.
[0093] The remainder of the chemical composition of the hot-rolled steel sheet according to the present embodiment may be Fe and impurities. In the present embodiment, impurities refer to elements incorporated from raw materials such as ore, scrap, or the manufacturing environment, or elements intentionally added in trace amounts, and are permitted within a range that does not adversely affect the hot-rolled steel sheet according to the present embodiment.
[0094] The hot-rolled steel sheet according to the present embodiment may contain the following elements as optional elements in addition to the above elements. The lower limit of the content when the following optional elements are not contained is 0%. Each optional element will be described in detail below.
[0095] Ti: 0.005 to 0.380%
[0096] Nb: 0.005 to 0.100%
[0097] V: 0.005 to 0.500%
[0098] Since Ti, Nb, and V all precipitate as carbides or nitrides in steel and have the effect of refining the metal structure through the pinning effect, one or more of these elements may be included. In order to obtain the effect of the above action more reliably, it is desirable to have a Ti content of 0.005% or more, a Nb content of 0.005% or more, or a V content of 0.005% or more.
[0099] However, even if these elements are contained in excess, the effect of the above action becomes saturated and is not economically desirable. Therefore, the Ti content is set to 0.380% or less, the Nb content to 0.100% or less, and the V content to 0.500% or less.
[0100] Cu: 0.01 to 2.00%
[0101] Cr: 0.01 to 2.00%
[0102] Mo: 0.01 to 1.00%
[0103] Ni: 0.02 to 2.00%
[0104] B: 0.0001 to 0.0100%
[0105] Cu, Cr, Mo, Ni, and B all have the effect of increasing the quenching properties of hot-rolled steel sheets. In addition, Cr and Ni have the effect of stabilizing residual austenite, and Cu and Mo have the effect of increasing the strength of hot-rolled steel sheets by precipitating carbides in the steel. Furthermore, Ni has the effect of effectively suppressing grain boundary cracking of the slab caused by Cu when Cu is included. Therefore, one or more of these elements may be included.
[0106] As described above, Cu has the effect of increasing the quenchability of the steel sheet and precipitating as a carbide in the steel at low temperatures to increase the strength of the hot-rolled steel sheet. In order to obtain the effect of the above action more reliably, it is desirable to have a Cu content of 0.01% or more.
[0107] However, if the Cu content exceeds 2.00%, grain boundary cracking of the slab may occur. Therefore, the Cu content is kept below 2.00%.
[0108] As described above, Cr has the effect of increasing the quenching properties of the steel sheet and stabilizing the retained austenite. In order to obtain the effect of the above action more reliably, it is desirable to have a Cr content of 0.01% or more.
[0109] However, if the Cr content exceeds 2.00%, the chemical treatment properties of the hot-rolled steel sheet are significantly reduced. Therefore, the Cr content is kept at 2.00% or less.
[0110] As described above, Mo has the effect of increasing the quenchability of steel sheets and the effect of increasing strength by precipitating carbides in the steel. In order to obtain the effect of the above action more reliably, it is desirable to have a Mo content of 0.01% or more.
[0111] However, even if the Mo content exceeds 1.00%, the effect of the above action becomes saturated and is not economically desirable. Therefore, the Mo content is kept at 1.00% or less.
[0112] As described above, Ni has the effect of increasing the quenchability of the steel sheet. In addition, when Cu is included, Ni has the effect of effectively suppressing grain boundary cracking of the slab caused by Cu. To obtain the effect of the above action more reliably, it is desirable to have a Ni content of 0.02% or more.
[0113] Since Ni is an expensive element, it is not economically desirable to include it in large quantities. Therefore, the Ni content is kept below 2.00%.
[0114] As described above, B has the effect of increasing the quenchability of the steel sheet. In order to obtain the effect of this action more reliably, it is desirable to have a B content of 0.0001% or more.
[0115] However, if the B content exceeds 0.0100%, the ductility of the hot-rolled steel sheet is significantly reduced, so the B content is kept below 0.0100%.
[0116] Ca: 0.0005 to 0.0200%
[0117] Mg: 0.0005 to 0.0200%
[0118] REM: 0.0005 to 0.1000%
[0119] Bi: 0.0005 to 0.020%
[0120] Ca, Mg, and REM all have the effect of improving the formability of hot-rolled steel sheets by controlling the shape of inclusions to a desirable shape. Additionally, Bi has the effect of improving the formability of hot-rolled steel sheets by refining the solidification structure. Therefore, one or more of these elements may be included. To obtain the effect of the above actions more reliably, it is desirable to have at least one of Ca, Mg, REM, and Bi in an amount of 0.0005% or more. However, if the Ca content or Mg content exceeds 0.0200%, or if the REM content exceeds 0.1000%, excessive inclusions are generated in the steel, which may actually reduce the ductility of the hot-rolled steel sheets. Furthermore, even if the Bi content exceeds 0.020%, the effect of the above actions becomes saturated, which is not economically desirable. Accordingly, the Ca content and Mg content are set to 0.0200% or less, the REM content to 0.1000% or less, and the Bi content to 0.020% or less. The Bi content is preferably 0.010% or less.
[0121] Here, REM refers to a total of 17 elements consisting of Sc, Y, and lanthanides, and the content of REM refers to the total content of these elements. In the case of lanthanides, they are added industrially in the form of misch metals.
[0122] One or more of Zr, Co, Zn, and W: 0 to 1.00% in total
[0123] Sn: 0 to 0.050%
[0124] With respect to Zr, Co, Zn, and W, the inventors have confirmed that the effect of the hot-rolled steel sheet according to the present embodiment is not impaired even if these elements are contained in a total of 1.00% or less. Therefore, one or more of Zr, Co, Zn, and W may be contained in a total of 1.00% or less.
[0125] In addition, the inventors confirmed that the effect of the hot-rolled steel sheet according to the present embodiment is not impaired even if a small amount of Sn is included, but since scratches may occur during hot rolling, the Sn content is 0.050% or less.
[0126] The chemical composition of the hot-rolled steel sheet described above can be measured by general analytical methods. For example, it can be measured using ICP-AES (Inductively Coupled Plasma-Atomic Emission Spectrometry). In addition, sol.Al can be measured by ICP-AES using the filtrate obtained after heating and decomposing the sample with acid. C and S can be measured using the combustion-infrared absorption method, N using the inert gas melting-thermal conductivity method, and O using the inert gas melting-non-dispersive infrared absorption method.
[0127] Metal structure of hot-rolled steel sheets
[0128] Next, the metal structure of the hot-rolled steel sheet according to the present embodiment will be described.
[0129] The hot-rolled steel sheet according to the present embodiment has a metallic structure composed of, in area %, bainite: 55 to 95%, retained austenite: 5 to 30%, fresh martensite: 5% or less, ferrite: 5% or less, and pearlite: 5% or less, and in the texture of the surface to a depth of 1 / 8 of the plate thickness from the surface, the extreme density of {110}<111> orientation is 3.0 or less.
[0130] In addition, in this embodiment, the area ratio of each microstructure at a depth of 1 / 4 of the plate thickness from the surface (an area from 1 / 8 of the plate thickness from the surface to 3 / 8 of the plate thickness from the surface) of the plate thickness cross-section parallel to the rolling direction is defined. This is because the metal structure at this position represents the typical metal structure of a hot-rolled steel sheet.
[0131] Bainite: 55 to 95%
[0132] Bainite is a structure that improves the strength and ductility of hot-rolled steel sheets. If the area percentage of bainite is less than 55%, the desired strength and ductility cannot be obtained in the hot-rolled steel sheet. Therefore, the area percentage of bainite is set to 55% or more. Preferably, it is 60% or more, 65% or more, or 70% or more.
[0133] Meanwhile, if the area ratio of bainite exceeds 95%, the desired ductility cannot be obtained. Therefore, the area ratio of bainite is set to 95% or less. Preferably, it is 92% or less, less than 90%, 90% or less, or 86% or less.
[0134] Retained austenite: 5 to 30%
[0135] Retained austenite is a structure that improves the ductility of hot-rolled steel sheets. If the area percentage of retained austenite is less than 5%, the desired ductility cannot be obtained in the hot-rolled steel sheet. Therefore, the area percentage of retained austenite is set to 5% or more. Preferably, it is 7% or more, more than 8%, 9% or more, 10% or more, 11% or more, 12% or more, 13% or more, 14% or more, or 15% or more.
[0136] Meanwhile, if the area percentage of retained austenite exceeds 30%, the desired strength cannot be obtained. Therefore, the area percentage of retained austenite is set to 30% or less. Preferably, it is 25% or less, or 23% or less.
[0137] Fresh martensite: 5% or less
[0138] Fresh martensite is a hard structure, so it contributes to improving the strength of hot-rolled steel sheets. However, fresh martensite is also a structure lacking ductility. If the area percentage of fresh martensite exceeds 5%, the desired ductility cannot be obtained in hot-rolled steel sheets. Therefore, the area percentage of fresh martensite is set to 5% or less. Preferably, it is 4% or less, 3% or less, or 2% or less. The area percentage of fresh martensite may be 0%.
[0139] Ferrite: 5% or less
[0140] Ferrite is a structure that improves the ductility of hot-rolled steel sheets but reduces their strength. If the area percentage of ferrite exceeds 5%, the desired strength cannot be obtained in the hot-rolled steel sheet. Therefore, the area percentage of ferrite is set to 5% or less. Preferably, it is 4% or less, 3% or less, or 2% or less. The area percentage of ferrite may be 0%.
[0141] Perlite: 5% or less
[0142] If the area percentage of pearlite is too high, the desired amount of retained austenite cannot be obtained. Therefore, the area percentage of pearlite is set to 5% or less. Preferably, it is 4% or less, 3% or less, or 2% or less. The area percentage of pearlite may be 0%.
[0143] Among each of the aforementioned structures, the area percentage of the structure other than the retained austenite is measured by the following method.
[0144] A test specimen is taken from a hot-rolled steel sheet so that the metal structure can be observed at a depth of 1 / 4 of the plate thickness from the surface (an area from 1 / 8 of the plate thickness from the surface to 3 / 8 of the plate thickness from the surface) of the plate thickness cross-section parallel to the rolling direction. Next, the plate thickness cross-section is polished, the polished surface is Nital etched, and the structure is observed in an area of 30 µm × 30 µm using an optical microscope and a scanning electron microscope (SEM). The observation area is set to at least three regions. By performing image analysis on the microstructure photographs obtained from this microstructure observation, the respective area percentages of ferrite, pearlite, and bainite are obtained. Subsequently, after performing etching on the same observation location, the microstructure is observed using an optical microscope and a scanning electron microscope, and the area percentage of fresh martensite is obtained by performing image analysis on the obtained microstructure photographs.
[0145] In the tissue observation described above, each tissue is identified by the following method.
[0146] Since fresh martensite has a high dislocation density and possesses substructures such as blocks or packets within the grains, it is possible to distinguish it from other metallic structures based on electron channeling contrast images using a scanning electron microscope.
[0147] A microstructure that is a collection of Rath-phase grains and does not contain Fe-based carbides with a long diameter of 20 nm or more within the microstructure, and is not a fresh martensite microstructure, or a microstructure that contains Fe-based carbides with a long diameter of 20 nm or more within the microstructure, and wherein the Fe-based carbides have a single variant, that is, Fe-based carbides elongated in the same direction, is considered as bainite. Here, Fe-based carbides elongated in the same direction means that the difference in the elongation direction of the Fe-based carbides is within 5°.
[0148] A structure consisting of massive crystal grains that does not contain substructures such as lath within the structure is considered to be ferrite.
[0149] A structure in which plate-like ferrite and Fe-based carbides are layered is considered to be pearlite.
[0150] The area percentage of retained austenite is measured by the following method.
[0151] In this embodiment, the area percentage of retained austenite is measured by X-ray diffraction. First, in a cross-section of the plate thickness parallel to the rolling direction of the hot-rolled steel sheet, at a depth of 1 / 4 of the plate thickness from the surface (an area from 1 / 8 of the plate thickness from the surface to 3 / 8 of the plate thickness from the surface), the integrated intensity of a total of 6 peaks of α (110), α (200), α (211), γ (111), γ (200), and γ (220) is obtained using Co-Kα rays, and the volume percentage of retained austenite is calculated using the intensity average method. The volume percentage of retained austenite obtained by this is considered as the area percentage of retained austenite.
[0152] Extreme density of {110}<111> orientation in the texture of the surface to a depth of 1 / 8 of the plate thickness from the surface: 3.0 or less
[0153] If the extreme density of {110}<111> orientation in the texture of the surface or the region at a depth of 1 / 8 of the plate thickness from the surface (hereinafter referred to as the surface layer region) exceeds 3.0, the bendability of the hot-rolled steel sheet deteriorates. Therefore, the extreme density of {110}<111> orientation in the surface layer region is set to 3.0 or less. Preferably, it is 2.8 or less, 2.5 or less, or 2.3 or less.
[0154] The lower limit is not specifically limited, but the extreme density of {110}<111> orientation in the texture of the surface area may be 0.7 or higher, or 1.0 or higher.
[0155] The ultra-density is determined using an EBSD device that combines a scanning electron microscope and an EBSD analysis device, and OIM Analysis (registered trademark) manufactured by AMETEK. From the Orientation Distribution Function (ODF) representing the three-dimensional texture, which is calculated by using the orientation data measured by the Electron Back Scattering Diffraction (EBSD) method and a spherical harmonic function, the ultra-density of the {110}<111> orientation in the φ2=45° cross-section of the texture in the surface region is determined.
[0156] In addition, the measurement range is set to an area from the surface to a depth of 1 / 8 of the plate thickness from the surface. The measurement pitch is set to 5㎛ / step.
[0157] {hkl} represents a crystal plane parallel to the rolling plane, and <uvw> represents a crystal direction parallel to the rolling direction. That is, {hkl}<uvw> represents a crystal in which {hkl> is oriented in the direction of the plate plane normal and <uvw> is oriented in the direction of the rolling.
[0158] In addition, the rolling direction of the hot-rolled steel sheet can be determined by the following method.
[0159] First, a test specimen is taken to observe the cross-section of the plate thickness of the hot-rolled steel sheet. After finishing the cross-section of the plate thickness of the taken specimen with mirror polishing, it is observed using an optical microscope. The observation range is set to the entire thickness of the plate, and the direction parallel to the grain elongation direction is determined as the rolling direction.
[0160] Arithmetic mean surface roughness Ra after pickling: Less than 1.2㎛
[0161] The hot-rolled steel sheet according to the present embodiment has an arithmetic mean surface roughness Ra of less than 1.2 μm after pickling. If the arithmetic mean surface roughness Ra of 1.2 μm or more after pickling, the bendability of the hot-rolled steel sheet decreases. Therefore, the arithmetic mean surface roughness Ra of 1.2 μm after pickling is made less than 1.2 μm. Preferably, it is 1.1 μm or less, 1.0 μm or less, 0.9 μm or less, 0.8 μm or less, or 0.7 μm or less.
[0162] The lower limit of the arithmetic mean roughness Ra of the surface after pickling is not specifically limited, but it may be 0.3 μm or more.
[0163] The arithmetic mean roughness Ra of the surface after pickling is measured by the following method.
[0164] First, the hot-rolled steel sheet is pickled by the following method.
[0165] Pickling treatment may be performed using conventional methods, for example, by immersing the material in hydrochloric acid with a concentration of 3 to 10 volume% at a temperature of 85 to 98°C for 20 to 300 seconds. Additionally, pickling may be performed once, or divided into multiple times as needed. The above pickling time (20 to 300 seconds) refers to the time of the pickling process when performed only once, and the total time of the pickling processes when performed multiple times. It is preferable to make the pickling temperature 85°C or higher so that oxides on the surface layer can be sufficiently removed. Although there is no specific upper limit for the pickling temperature, in practice it is approximately 98°C. If the pickling time exceeds 300 seconds, the surface roughness becomes excessively rough, the surface properties deteriorate, and additionally, irregularities remaining after cold rolling may produce a notch-like effect, which may deteriorate the bendability of the hot-rolled steel sheet. The upper limit of the pickling time is preferably 200 seconds.
[0166] Next, a sample of 1000 mm × 1000 mm is taken from the hot-rolled steel sheet after pickling. On the surface of the sample, measurement points are set at intervals of 200 mm in the rolling direction and the plate width direction, and the surface roughness is measured at each measurement point. However, the measurement length at each measurement point is set to 5 mm. A roughness curve is obtained by sequentially applying contour curve filters with cutoff values λc and λs to the measurement cross-sectional curve obtained from the measurement. Specifically, from the obtained measurement results, components with a wavelength λc of 0.8 mm or less and components with a wavelength λs of 2.5 μm or more are removed to obtain the roughness curve. Based on the obtained roughness curve, the arithmetic mean roughness Ra of each measurement point is calculated in accordance with JIS B 0601:2013. The arithmetic mean roughness Ra of the surface is obtained by calculating the average value of the measurements obtained at each measurement point.
[0167] In cases where the hot-rolled steel sheet has a surface treatment film, such as plating or painting, on its surface, the arithmetic mean roughness Ra is measured after performing the pickling described above on the surface of the steel obtained after removing the surface treatment film from the hot-rolled steel sheet. The method for removing the surface treatment film can be appropriately selected according to the type of surface treatment film within a range that does not affect the surface roughness of the steel. For example, if the surface treatment film is a zinc plating layer, the zinc plating layer can be dissolved using dilute hydrochloric acid to which an inhibitor has been added. By doing so, only the zinc plating layer can be peeled off from the steel sheet. An inhibitor is an additive used to suppress changes in roughness caused by preventing over-dissolution of the steel. For example, a solution can be used in which the corrosion inhibitor "Evit No. 700BK" for hydrochloric acid pickling manufactured by Asahi Kagaku Kogyo Co., Ltd. is added to hydrochloric acid diluted 10 to 100 times to a concentration of 0.6 g / L.
[0168] Machine characteristics
[0169] The hot-rolled steel sheet according to the present embodiment may have a tensile (maximum) strength of 980 MPa or more. By making the tensile strength 980 MPa or more, it can further contribute to the weight reduction of the vehicle body. More preferably, the tensile strength is 1180 MPa or more. Although there is no need to specifically limit the upper limit, it may be 1470 MPa.
[0170] The product of tensile strength and uniform elongation (TS × uEl), which is an indicator of ductility, may be 8260 MPa·% or more.
[0171] The limit bending R / t, which is an indicator of bendability, may be 1.80 or less.
[0172] Tensile strength TS and uniform elongation uEl are measured by performing a tensile test in accordance with JIS Z 2241:2011 using a No. 5 specimen of JIS Z 2241:2011. The sampling location for the tensile test specimen should be set to the 1 / 4 portion from the end in the plate width direction, and the direction perpendicular to the rolling direction should be the length direction.
[0173] The limit bending R / t is evaluated by the following bending tests.
[0174] A rectangular test specimen of 100 mm × 30 mm is cut from the 1 / 4 portion of the end in the width direction of the hot-rolled steel sheet. For both bending where the bending ridge is parallel to the rolling direction (L direction) (L-axis bending) and bending where the bending ridge is parallel to the direction perpendicular to the rolling direction (C direction) (C-axis bending), a bending test is performed in accordance with the V-block method of JIS Z 2248:2006 (bending angle is 90°) to determine the minimum bending radius at which no crack occurs. The limit bending R / t is obtained by calculating the value obtained by dividing the average value of the minimum bending radii of the L-axis and C-axis by the plate thickness.
[0175] In addition, the rolling direction of the hot-rolled steel sheet can be determined by the method described above.
[0176] However, the presence or absence of cracks is determined by mirror polishing a cross-section of a specimen cut from a plane perpendicular to the plate plane and parallel to the bending direction after the bending test, and observing the cracks with an optical microscope; if the crack length observed on the inner side of the bend of the specimen exceeds 30 μm, it is determined that there are cracks.
[0177] Plate thickness
[0178] The thickness of the hot-rolled steel sheet according to the present embodiment is not particularly limited, but may be 0.5 to 8.0 mm. By making the thickness of the hot-rolled steel sheet 0.5 mm or more, it becomes easier to secure the rolling completion temperature and reduce the rolling load, thereby facilitating hot rolling. Therefore, the thickness of the hot-rolled steel sheet according to the present embodiment may be 0.5 mm or more. Preferably, it is 1.2 mm or more and 1.4 mm or more. In addition, by making the thickness 8.0 mm or less, it becomes easier to refine the metal structure, and the metal structure described above can be easily secured. Therefore, the thickness may be 8.0 mm or less. Preferably, it is 6.0 mm or less.
[0179] plating layer
[0180] The hot-rolled steel sheet according to the present embodiment having the chemical composition and metal structure described above may be provided with a plating layer on its surface for the purpose of improving corrosion resistance, etc., and may be a surface-treated steel sheet. The plating layer may be an electroplated layer or a hot-dip plating layer. Examples of the electroplated layer include electro-galvanizing and electro-Zn-Ni alloy plating. Examples of the hot-dip plating layer include hot-dip galvanizing, alloyed hot-dip galvanizing, hot-dip aluminum plating, hot-dip Zn-Al alloy plating, hot-dip Zn-Al-Mg alloy plating, and hot-dip Zn-Al-Mg-Si alloy plating. The amount of plating applied is not particularly limited and may be performed in the same manner as in the past. In addition, it is possible to further improve corrosion resistance by performing a suitable chemical treatment (e.g., application and drying of a silicate-based chromium-free chemical treatment solution) after plating.
[0181] Manufacturing conditions
[0182] In a suitable manufacturing method for hot-rolled steel sheets according to the present embodiment, the following processes (1) to (8) are performed sequentially. By adopting the following manufacturing method, hot-rolled steel sheets according to the present embodiment can be manufactured stably.
[0183] In addition, the temperature of the slab and the temperature of the steel plate in this embodiment refer to the surface temperature of the slab and the surface temperature of the steel plate. In this embodiment, the temperature of the hot-rolled steel plate is measured using a contact or non-contact thermometer at the shortest part in the plate width direction. At parts other than the shortest part in the plate width direction of the hot-rolled steel plate, it is measured by a thermocouple or calculated by heat transfer analysis.
[0184] (1) A slab having the chemical composition described above is heated to a temperature range of 1170°C or higher and maintained in the said temperature range.
[0185] (2) Rough rolling is performed so that the final reduction rate is 30% or less.
[0186] (3) The maximum temperature from the completion of rough rolling until descaling before finishing rolling is set to T1 (°C) or higher, expressed by the following formula (A) or formula (B).
[0187] When Al / Si = a,
[0188] In the case where a≤1 / 3,
[0189]
[0190] In the case where a > 1 / 3,
[0191]
[0192] However, each element symbol indicates the content in mass % of the corresponding element.
[0193] (4) After rough rolling is completed and before finishing rolling, descaling is performed with an impact pressure of 2.5 MPa or more.
[0194] (5) Finish rolling is performed such that the finishing rolling completion temperature is T2(°C) or higher as expressed by the following formula (C), and the cumulative reduction rate of the rolling from the final stage to the stage before the final stage is less than 30%.
[0195]
[0196] However, each element symbol represents the content of the corresponding element in mass %, and if the corresponding element is not contained, 0 is substituted.
[0197] (6) Cool to a temperature range of 350 to 450°C at an average cooling rate of 30°C / s or more.
[0198] (7) It is wound in a temperature range of 350 to 450°C.
[0199] (8) The average cooling rate up to a temperature range of 150℃ or lower is set to 15 to 40℃ / h.
[0200] (1) Slab heating
[0201] The slabs provided for hot rolling may be slabs obtained by continuous casting or slabs obtained by casting and ingots. If necessary, slabs that have undergone hot or cold working may be used. It is preferable to heat the slabs provided for hot rolling to a temperature range of 1170°C or higher. Furthermore, it is more preferable to maintain them in this temperature range for 6000 seconds or more. By heating to the above temperature range, a desired arithmetic mean roughness Ra can be obtained on the surface after pickling.
[0202] For hot rolling, it is preferable to use a reverse mill or a tandem mill as a multi-pass rolling. Particularly from the perspective of industrial productivity, it is more preferable to perform hot rolling using a tandem mill for at least the final stage.
[0203] (2) Rough rolling
[0204] In rough rolling, it is desirable to keep the final reduction ratio (final reduction ratio) 30% or less. By keeping the final reduction ratio 30% or less, a desired arithmetic mean roughness Ra can be obtained on the surface after pickling.
[0205] The final reduction ratio can be expressed as (t0-t1) / t0×100(%), where t0 is the thickness of the inlet plate of the final stage and t1 is the thickness of the outlet plate after rolling of the final stage.
[0206] (3) The highest temperature from the completion of rough rolling to the descaling before the finishing rolling.
[0207] It is preferable that the maximum temperature from the completion of rough rolling until descaling before finishing rolling be at least T1(°C) as expressed by the above equation (A) or the above equation (B). By making the maximum temperature at least T1(°C), a desired arithmetic mean roughness Ra can be obtained on the surface after pickling.
[0208] (4) Descaling before finishing rolling
[0209] After the completion of rough rolling and before the finish rolling, it is desirable to perform descaling with an impact pressure of 2.5 MPa or higher. Descaling is a process of removing scale formed on the surface of a steel plate by spraying water onto the upper and lower surfaces of the steel plate using nozzles. When descaling is performed by spraying water using multiple nozzles, it is desirable to control the maximum impact pressure among the multiple nozzles to be 2.5 MPa or higher. By performing descaling with an impact pressure of 2.5 MPa or higher, a desired arithmetic mean roughness Ra can be obtained on the surface after pickling.
[0210] To preferably control the texture of the surface area, it is desirable to perform descaling with an impact pressure of less than 3.0 MPa.
[0211] (5) Finish rolling
[0212] It is preferable that the finishing rolling be performed such that the finishing rolling completion temperature is T2(°C) or higher, as expressed by the above equation (C), and the cumulative reduction rate of the rolling between the final stage and the stage one step prior to the final stage is less than 30%. By making the finishing rolling completion temperature T2(°C) or higher, a desired texture can be obtained in the surface layer region. In addition, by making the cumulative reduction rate of the rolling between the final stage and the stage one step prior to the final stage less than 30%, a desired texture can be obtained in the surface layer region.
[0213] In addition, the finish rolling completion temperature refers to the exit temperature of the final stage of finish rolling. Furthermore, the cumulative reduction ratio of the final stage and the rolling one stage prior to the final stage can be expressed as (t0-t1) / t0×100(%), where the inlet plate thickness one stage prior to the final stage is t0 and the exit plate thickness of the final stage is t1.
[0214] (6) Cooling after finishing rolling
[0215] After the finishing rolling is completed, it is desirable to cool to a temperature range of 350 to 450°C at an average cooling rate of 30°C / s or more. By maintaining an average cooling rate of 30°C / s or more to the above temperature range, the formation of ferrite and pearlite can be suppressed. In addition, by performing the cooling to a temperature range of 350 to 450°C, coiling can be performed at a desired temperature range.
[0216] In addition, the average cooling rate referred to in this embodiment is a value obtained by dividing the temperature difference between the start of cooling and the end of cooling by the elapsed time from the start of cooling to the end of cooling.
[0217] (7) Winding
[0218] It is preferable to set the coiling temperature to a temperature range of 350 to 450°C. By coiling in this temperature range, the excessive precipitation of fresh martensite can be suppressed, thereby allowing the desired amount of bainite to be obtained. Additionally, the desired amount of retained austenite can be obtained.
[0219] (8) Cooling after winding
[0220] After coiling, it is preferable to cool to a temperature range of 150°C or lower at an average cooling rate of 15 to 40°C / h. By cooling at an average cooling rate of 15°C / h or higher, carbon can be enriched in the retained austenite, thereby stabilizing the retained austenite. As a result, a desired amount of retained austenite can be obtained. The average cooling rate is more preferably 20°C / h or higher. Additionally, by cooling at an average cooling rate of 40°C / h or lower, the formation of fresh martensite can be suppressed, thereby obtaining a desired amount of bainite. Furthermore, the average cooling rate is more preferably less than 30°C / h.
[0221] In addition, the average cooling rate after winding can be controlled by means of a thermal insulation cover, edge mask, mist cooling, etc.
[0222] Examples
[0223] Next, the effects of one embodiment of the present invention will be explained in more detail by way of examples. However, the conditions in the examples are examples of conditions adopted to verify the feasibility and effects of the present invention, and the present invention is not limited to these examples of conditions. The present invention may adopt various conditions as long as the objectives of the present invention are achieved without departing from the gist of the present invention.
[0224] Steel having the chemical compositions shown in Tables 1 and 2 was melted, and slabs with a thickness of 240 to 300 mm were manufactured by continuous casting. Using the obtained slabs, hot-rolled steel sheets were obtained under the manufacturing conditions shown in Tables 3 and 4.
[0225] In addition, prior to hot rolling, the slab was heated to the heating temperature listed in Tables 3 and 4 and maintained for at least 6,000 seconds. For descaling prior to finish rolling, the impact pressure was set to approximately 2.8 MPa. Furthermore, cooling after coiling was carried out down to a temperature range of 150°C or lower at the average cooling rate listed in Tables 3 and 4.
[0226] For the obtained hot-rolled steel sheet, the area percentage of each microstructure, ultradensity, arithmetic mean surface roughness Ra after pickling, tensile strength TS, uniform elongation uEl, and limit bending R / t were measured by the method described above. In addition, the arithmetic mean surface roughness Ra after pickling was obtained by measuring the hot-rolled steel sheet after pickling by the method described above. In addition, the tensile strength TS, uniform elongation uEl, and limit bending R / t were obtained by measuring the hot-rolled steel sheet after pickling by the method described above.
[0227] metewand
[0228] If the tensile strength TS is 980 MPa or higher, it was judged to be acceptable as it has high strength. On the other hand, if the tensile strength TS is less than 980 MPa, it was judged to be unacceptable as it does not have high strength.
[0229] When the product of tensile strength TS and uniform elongation uEl (TS × uEl) is 8260 MPa·% or higher, it is judged to have excellent ductility and pass. On the other hand, when TS × uEl is less than 8260 MPa·%, it is judged to have not excellent ductility and pass.
[0230] When the limit bending R / t is 1.80 or less, it was judged to have excellent bendability and passed. On the other hand, when the limit bending R / t is greater than 1.80, it was judged to have poor bendability and failed.
[0231]
[0232]
[0233]
[0234]
[0235]
[0236]
[0237] As can be seen from Tables 5 and 6, in the example of the present invention, a hot-rolled steel sheet having high strength and excellent ductility and bendability was obtained.
[0238] Meanwhile, in the comparative example, it can be seen that one or more of the above characteristics have decreased. Industrial applicability
[0239] According to the above embodiment of the present invention, a hot-rolled steel sheet having high strength and excellent ductility and bendability can be provided.
Claims
Claim 1 The chemical composition, in mass%, is C: 0.100 to 0.350%, Si: 0.30 to 3.00%, Mn: 1.00 to 4.00%, sol.Al: 0.001 to 2.000%, Si+sol.Al: 1.00 to 5.00%, P: 0.100% or less, S: 0.0300% or less, N: 0.1000% or less, O: 0.0100% or less, Ti: 0 to 0.380%, Nb: 0 to 0.100%, V: 0 to 0.500%, Cu: 0 to 2.00%, Cr: 0 to 2.00%, Mo: 0 to 1.00%, Ni: 0 to 2.00%, B: 0 to Containing 0.0100%, Ca: 0 to 0.0200%, Mg: 0 to 0.0200%, REM: 0 to 0.1000%, Bi: 0 to 0.020%, one or more of Zr, Co, Zn and W: 0 to 1.00% in total, and Sn: 0 to 0.050%, with the remainder being Fe and impurities; the metal structure is composed, in area %, of bainite: 55 to 95%, retained austenite: 5 to 30%, fresh martensite: 5% or less, ferrite: 5% or less, and pearlite: 5% or less; in the texture of the surface to a depth of 1 / 8 of the plate thickness from the surface, the polar density of {110}<111> orientation is 3.0 or less, and the arithmetic mean roughness of the surface after pickling Hot-rolled steel sheet characterized by Ra being less than 1.2㎛. Claim 2 The chemical composition of claim 1 is characterized by containing, in mass%, one or more types selected from the group consisting of Ti: 0.005 to 0.380%, Nb: 0.005 to 0.100%, V: 0.005 to 0.500%, Cu: 0.01 to 2.00%, Cr: 0.01 to 2.00%, Mo: 0.01 to 1.00%, Ni: 0.02 to 2.00%, B: 0.0001 to 0.0100%, Ca: 0.0005 to 0.0200%, Mg: 0.0005 to 0.0200%, REM: 0.0005 to 0.1000%, and Bi: 0.0005 to 0.020%. Hot-rolled steel sheet.
Citation Information
Patent Citations
hot rolled steel plate
KR1020210079342A
High-strength hot-rolled steel sheet and method for manufacturing same
WO2020250735A1